INFORMATION SYSTEM OF ACCOUNTING FOR PROFESSIONAL DEVELOPMENT OF EDUCATORS IN FORMAL AND NON-FORMAL EDUCATION - Pokryshen, Dmytro (Physical and Mathematical Education, 2021)
Formulation of the problem. The article is devoted to the possibility of conducting centralized or regional accounting of professional development of educators, recognition of learning outcomes of various subjects of professional development. The review and analysis of the structure of the information system of accounting for professional development of educators in formal and non-formal education is made, its structural components are characterized. The purpose of its use is determined. An ER model of such a system has been designed. The system of data access and the level of its distribution are determined. Materials and methods. To achieve this goal, the following research methods were used: theoretical - analysis of legal documents relating to the system of teacher training; generalization of best practices in business documentation, accounting for issued certificates; analysis and systematization of functional responsibilities in educational institutions; diagnostic - research of structure of a database of the account of documents on passing of advanced training for the purpose of necessary structure; analysis of the activities of persons keeping records. Results. The proposed structure of the information system of accounting for professional development of educators in formal and non-formal education provides for the need to preserve information about the educator, the subject of professional development, acquired competencies and documents received. The structure of each entity is proposed, the indices and the relationship between the components are defined. The information system needs to define users and access rights. Access to the table with information on professional development of educators should be open. This is necessary so that stakeholders and other educators can see how a teacher is involved in professional development. Data entry is provided through authenticated authorized access of the employee responsible for advanced training (internship) and certification. This person has the necessary data about educators, enters this information into the database. Conclusions. The functioning of such a regional or all-Ukrainian information system for accounting for professional development of educators in formal and non-formal education will address a number of issues arising in the certification and certification of educators.